2019
DOI: 10.1103/physrevb.99.144522
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb problem in iron-based superconductors

Abstract: We discuss the role of strong Coulomb interactions in iron-based superconductors (FeSCs). The presumed s ± character of these superconductors means that the condensate is not symmetry protected against Coulomb repulsion. Remarkably, the transition temperatures and the excitation gap are quite robust across the large family of iron based superconductors, despite drastic changes in Fermi surface geometry. The Coulomb problem is to understand how these superconductors avoid the strong onsite Coulomb interaction a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Figure 1 estimates the error of the theoretical Tc by tuning μ*. Despite the calculation of μ* as a function of Debye temperature and Fermi level [42] may not be very accurate in such a strongly correlated electron system [43], it has been argued that for the most Fe-based superconductors μ* should be 0.15-0.2 [44]. The error of our Tc calculation due to the uncertainty of μ * is within ~15%.…”
Section: Resultsmentioning
confidence: 91%
“…Figure 1 estimates the error of the theoretical Tc by tuning μ*. Despite the calculation of μ* as a function of Debye temperature and Fermi level [42] may not be very accurate in such a strongly correlated electron system [43], it has been argued that for the most Fe-based superconductors μ* should be 0.15-0.2 [44]. The error of our Tc calculation due to the uncertainty of μ * is within ~15%.…”
Section: Resultsmentioning
confidence: 91%
“…Figure 1 estimates the error of the theoretical T c by tuning μ* . Despite that the calculation of μ* as a function of Debye temperature and Fermi level [ 41 ] may not be very accurate in such a strongly correlated electron system [ 42 ], it has been argued that for the most Fe-based superconductors, μ * should be 0.15–0.2 [ 12 ]. In this paper, we choose the value ( µ * = 0.15) of the Coulomb pseudopotential to calculate the T c of LiFeAs, NaFeAs and FeSe to make a fair comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, we set and . Although the accuracy of calculating the pseudopotential for a strongly correlated electron system, such as Fe-based superconductors, as a function of Debye temperature and Fermi level, 36 may not be very precise, it has been suggested that the value should be approximately 0.15 for most Fe-based superconductors. 36 We put the ab-initio details in the supplemental information .…”
Section: Methodsmentioning
confidence: 99%